2018
DOI: 10.3390/microorganisms6010003
|View full text |Cite
|
Sign up to set email alerts
|

Pichia pastoris is a Suitable Host for the Heterologous Expression of Predicted Class I and Class II Hydrophobins for Discovery, Study, and Application in Biotechnology

Abstract: The heterologous expression of proteins is often a crucial first step in not only investigating their function, but also in their industrial application. The functional assembly and aggregation of hydrophobins offers intriguing biotechnological applications from surface modification to drug delivery, yet make developing systems for their heterologous expression challenging. In this article, we describe the development of Pichia pastoris KM71H strains capable of solubly producing the full set of predicted Cordy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 55 publications
(75 reference statements)
0
11
0
3
Order By: Relevance
“…It should be noted that with the decrease in sequencing costs, each year more fungal genomes are discovered, which is why the current division may become out of date. The search of databases confirms that class II hydrophobins are present only in Ascomycota as a homogeneous group in the phylogenetic tree [23,59] (Fig. 2).…”
Section: Classification Of Hydrophobinsmentioning
confidence: 56%
See 3 more Smart Citations
“…It should be noted that with the decrease in sequencing costs, each year more fungal genomes are discovered, which is why the current division may become out of date. The search of databases confirms that class II hydrophobins are present only in Ascomycota as a homogeneous group in the phylogenetic tree [23,59] (Fig. 2).…”
Section: Classification Of Hydrophobinsmentioning
confidence: 56%
“…The research conducted on the HGFI hydrophobin from Grifola frondosa and hydrophobins produced by Pleurotus ostreatus using an atomic force microscope (AFM) has shown that the length of tubular fibres is from 50 to 105 nm, and the width ranges from 19 to 24 nm. The rodlet layers take the form of a double layer [23,41,49,88,89]. In 2013, Stanimirova et al [68] conducted a series of experiments aimed at demonstrating changes in surface pressure during the formation of the hydrophobic film.…”
Section: Properties Of Hydrophobinsmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenotype of colony used for insulin Aspart precursor production is Mut S which has slow ability to utilize methanol as sole carbon source. Mut S phenotype enables methanol accumulation for promoter activation in shake flask culture since the methanol is supplied once daily (Gandier and Master, 2018). The provided methanol in the medium will not be rapidly utilized to accelerate its growth but will be used instead for promoter induction.…”
Section: Optimization Of Insulin Aspart Precursor Productionmentioning
confidence: 99%